Musical-Artistic Events of Young Students as a Factor in Strengthening Intra-community Partnerships - Diana Elena SÂRB; Loredana MUNTEAN (Studia Universitatis Babeş-Bolyai. Musica)
This paper aims to highlight the importance of musical-artistic events organized in schools and communities from the perspective of fostering lifelong artistic competencies. The study seeks to identify the attitudes of primary school teachers toward musical-artistic events through an applied questionnaire. To assess the extent to which such events contribute to the development of artistic competencies and the strengthening of school-family-community partnerships, an exploratory study based on a questionnaire administered to primary education teachers was conducted.